Disclosures of materiality: the practice of Malaysian companies - Takiah Mohd. Iskandar,; Syed Mohd. Ghazali Wafa Syed Adwam Wafa,; Selamat Kundari,; Rosiati Ramli, (Penerbit Universiti Kebangsaan Malaysia, 1998)
The reporting of information in the financial statements is pervasively based on the materiality concept. For the purpose of disclosing financial information, auditors use their professional judgments in deciding the appropriate materiality thresholds. There is evidence of a lack of consensus in disclosure thresholds that researchers and practitioners believe to have arisen from the absence of a clear guideline on materiality. This study uses an archival approach to provide empirical evidence of materiality thresholds for the disclosure of financial informatzon among companies in the retall and finance industries in Malaysia. Results show that the threshold of a majority of the disclosed items being examined is very low (i.e., below 5% of net profit for the current year). The study found a significant difference in disclosure threshold between industries. The study suggests that specific guidelines on materiality threshold for different industries should be established for the disclosure of financcal items.